1956
DOI: 10.1037/h0041782
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of the role of psychological factors in the production of gastric ulcers in rats.

Abstract: Systematic variation of electric shock, hunger, thirst and the approach-avoidance conflict which had previously been shown capable of producing gastric ulcers in rats indicated (a) conflict to be a significant variable, (b) hunger and shock to contribute significantly in interaction, (c) thirst to fail of significance, and (d) that though weight loss is significantly related to the hunger, thirst and shock variables, it was not directly related to ulcer formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
1

Year Published

1966
1966
1987
1987

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 2 publications
(5 reference statements)
2
29
1
Order By: Relevance
“…Results of the present study were in agreement with the findings of Sawrey & Sawrey (1964), in that a es previously paired with shock onset and then presented during restraint resulted in a greater number of gastric lesions than did a control es. In the present study, lesion frequency did appear to be a measure that differentiated between the effects of the es presented at shock onset and the effects of the es paired with shock termination.…”
Section: Diseussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Results of the present study were in agreement with the findings of Sawrey & Sawrey (1964), in that a es previously paired with shock onset and then presented during restraint resulted in a greater number of gastric lesions than did a control es. In the present study, lesion frequency did appear to be a measure that differentiated between the effects of the es presented at shock onset and the effects of the es paired with shock termination.…”
Section: Diseussionsupporting
confidence: 83%
“…These investigators found a higher frequency of gastric lesions when the es paired with onset of electric shock was later presented to rats under physical restraint than when a backwardeonditioned es (control) was presented during restraint. Sawrey & Sawrey (1964) suggested that sinee restraint-induced gastric lesions occur in response to changes in autonomic funetioning, then frequency of lesions may be an indirect measure of autonomic conditioning in response to the presentation of a es with negatively reinforcing properties. It was further suggested that frequency of gastric lesions may be a more direct measure of the effects of the negative reinforeing properties of this es than the measurements used in an instrumental conditioning situation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results concerning the attenuating effect of punishment on gastric lesions seem to be incompatible with those attenuates gastric lesions of previous studies (Sawrey et al, 1956;Weiss, 1971). Two possibilities can be proposed to explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 56%
“…The previous studies revealed that the animals receiving punishment for foodmotivated responses showed greater gastric lesions (mainly in the upper portion of stomach) than did the control animals exposed to response-noncontingent shock (Sawrey, Conger, & Turrell, 1956;Weisz, 1957;Pare & Livingston, 1970). It was also found in the previous studies that the animals receiving punishment for avoidance-escape responses from the electric shock showed more severe gastric lesions than did the control animals received the response-noncontingent shock (Weiss, 1971;Wald, Mackinnon, & Desiderato, 1973).…”
mentioning
confidence: 53%